Quality of life among sports practitioning medicine students (Research, Society and Development, 2023)
Introduction: quality of life (QoL) is defined as the individual's perception of their life context, with regard to culture, values within society, and in relation to their goals, expectations, standards and concerns. Furthermore, the practice of physical activity, in addition to leading to an increase in quality of life, can positively impact the lives of medical students. Objectives: to compare the quality of life between medical students who practice sports and those who do not. Methodology: cross-sectional observational study. The research population consisted of 256 medical students from a University Center in Teresina-PI. Data collection was performed using a sociodemographic questionnaire and the application of the WHOQOL-bref scale. To compare aspects of life and quality of life, independent t-tests and ANOVA were applied. Results: the results showed that among the sports practiced by the students, bodybuilding had a practice of 71.5% and 153 participants in relation to the other sports. In addition, it was observed that among the basic, clinical and internship cycles, the clinical cycle had a higher score compared to the basic one and the environment domain prevailed compared to the others. The largest participation was of women and students aged over 20 years. Conclusion: it can be concluded that the domains that obtained the highest averages were those who practiced physical exercises, showing that the practice of physical activity tends to bring beneficial changes to the practitioner's quality of life.